Pressure distributions on swept/unswept wings using pressure sensitive paint. (April 2020) - Huang, Y.X.; Wu, H.Y.; Chung, K. M.; Chang, K.C.
Abstract: Pressure sensitive paint (PSP) is an optical-based technique for full-field pressure measurements. A polymer-ceramic PSP, Ru(dpp), with a porous material is used and is applied onto a Mylar tape which affixed to the model surface of NACA 0012 and ONERA M6 wings. The PSP results agree with the data using conventional pressure measurements reasonably well.